Influence of HRM Practices on Employee Job Satisfaction: Evidence from Commercial Banks in Nepal - Raut, Hiralal (Academic Voices: A Multidisciplinary Journal, 2018)
The purpose of the study is to investigate the influence of HRM practices on employees’ job satisfaction and find out the degree of association between HRM practices and job satisfaction. In this research study both exploratory and descriptive research design use to get the response from 80 respondents from 20 commercial banks of Birgunj, Nepal was surveyed conveniently through a structured questionnaire, then the responses were analyzed by conducting a test of hypothesis, correlation and regression analysis using SPSS software. Correlation analysis reveals that HRM practices have a significant relationship with job satisfaction, besides regression analysis shows that the five factors of HRM practices depicted in the model explains about 57.3 percent of job satisfaction among the bank employees and have a positive influence on their job satisfaction. It has also been found that work-life balance practices (WLBP), compensation and reward (CNR), recruitment and selection (RNS) have the most influence on job satisfaction (JS). Thus, findings of this study will provide new insights to the bank managers about the way to ensure job satisfaction of employees and thereby to boost their commitment and performance.